A new subfamily classification of the Citrus family (Rutaceae) based on six nuclear and plastid markers. Issue 5 (16th July 2021) - Appelhans, Marc S.; Bayly, Michael J.; Heslewood, Margaret M.; Groppo, Milton; Verboom, G. Anthony; Forster, Paul I.; Kallunki, Jacquelyn A.; Duretto, Marco F.
Abstract: Rutaceae is a family of angiosperms well known for the economically important genus Citrus . The division of Rutaceae into subfamilies is still inadequate and provisional. Previous phylogenetic studies at the family level are characterized by a limited sampling of genera and lack several crucial taxa. Here, we present a phylogenetic study based on six nuclear and plastid markers including 87.7% of the currently accepted genera, which is more than twice as many as in previous studies. Seven genera are included in a phylogenetic analysis for the first time. Most clades are resolved with high support, and we propose a new subfamily classification for Rutaceae that comprises the subfamilies Amyridoideae, Aurantioideae, Cneoroideae, Haplophylloideae, Rutoideae and Zanthoxyloideae. Aurantioideae is the only traditional subfamily that is resolved as monophyletic. We tested whether 13 morphological and karyological characters are taxonomically informative in Rutaceae. Chromosome numbers are clearly different in the two main clades of Rutaceae, but fruit characteristics, which have been used to define subfamilies in the past, do not distinguish between the main lineages of the family.